Conceptos alternativos para una sociedad crítica y pensante (2014)
Grupo de Investigación Interdisciplinario de Estudios Pedagógicos (GIDEP).-- Línea de Investigación: Pedagogías Críticas.-- Área: educación.-- Tema: pedagogía crítica para la formación. In this work we find important journal articles, books, citations on critical pedagogues who studied all his life looking for a socio-cultural change in order to improve education. Readers will discover the importance of language and respect for the academy, for personal and social growth of human beings. Being not born becomes and society is responsible to grow or stagnate in global development. In conclusion it may have a small critical essay on the state of education and training in Colombian society because of the monopoly, and racial or economic discrimination that idealizes educational standards leading them to an elite or ordinary people.